ANSWER
The correct answer is D.
![\sum_{n=1} ^{6} (n - 3) = ( - 2) + ( - 1) + (0) + (1) + (2) + (3) = 3](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29%20%3D%20%28%20-%202%29%20%2B%20%28%20-%201%29%20%2B%20%280%29%20%2B%20%281%29%20%2B%20%282%29%20%2B%20%283%29%20%3D%203)
EXPLANATION
The given expression is
![\sum_{n=1} ^{6} (n - 3)](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29)
The symbol means summation.
So we need to substitute
![n=1,n=2,n=3,n=4,n=5, \:and\:n=6](https://tex.z-dn.net/?f=n%3D1%2Cn%3D2%2Cn%3D3%2Cn%3D4%2Cn%3D5%2C%20%5C%3Aand%5C%3An%3D6)
into the formula and add all to get,
![\sum_{n=1} ^{6} (n - 3) = (1 - 3) + (2 - 3) + (3- 3) + (4 - 3) + (5 - 3) + (6 - 3)](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29%20%3D%20%281%20-%203%29%20%2B%20%282%20-%203%29%20%2B%20%283-%203%29%20%2B%20%284%20-%203%29%20%2B%20%285%20-%203%29%20%2B%20%286%20-%203%29)
We simplify to obtain,
![\sum_{n=1} ^{6} (n - 3) = ( - 2) + ( - 1) + (0) + (1) + (2) + (3) = 3](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%3D1%7D%20%5E%7B6%7D%20%28n%20-%203%29%20%3D%20%28%20-%202%29%20%2B%20%28%20-%201%29%20%2B%20%280%29%20%2B%20%281%29%20%2B%20%282%29%20%2B%20%283%29%20%3D%203)
The correct answer is D
Answer:
x = 75
Step-by-step explanation:
x/5 = 15
x = 75 Multiply 5 on both sides
So first you would have to work with the y's since they are consecutive angles.Consecutive angles would add up to 180 so the problem would be
5(y+11)^0+4y-10=180 then simplify
10+4y-10=180
4y=180
y=45
Then plug in the y for the top problem and the add the answer to the x problem and set them to 180 because they are also a linear pair and you should get your answer
I got x=34
The care has gone 60m in 12 seconds
Answer:
H
Step-by-step explanation: Report the one with the link